Chemical composition and in vitro antiobesity and in vivo anti-hyperlipidemic effects of Ceratotheca sesamoides, Jatropha tanjorensis, Mucuna flagellipes, Pterocarpus mildbraedii and Piper guineense - Gabriel O. Anyanwu; Dorathy Anzaku; Chinda C. Donwell; Usunomena Usunobun; Ademuyiwa J. Adegbegi; Patricia C. Ofoha; Khalid Rauf (Elsevier, 2021)
Ethnopharmacological relevance: Ceratotheca sesamoides, Jatropha tanjorensis, Mucuna flagellipes, Pterocarpus mildbraedii and Piper guineense are all medicinal plants found in West Africa and used traditionally for the treatment of various ailments such as; hypertension, arteriosclerosis, anemia, malaria and flatulence. Aim of the study: The purpose of this study is to ascertain the in vitro anti-obesity and in vivo anti-hyperlipidemic activity of extracts and fractions of selected plants. Materials and methods: The ethanolic extract of the aforementioned five plants were tested in vitro for their activity against porcine pancreatic lipase and alpha-amylase at a concentration of 1mg/ml. Thereafter, the IC50 values of the plants active against alpha-amylase were determined. The ethanolic extract of P. mildbraedii and M. flagellipes were fractionated using n-hexane, n-butanol, ethyl acetate and water, thus the four fractions each obtained were used for further in vitro and in vivo studies. Thirty-five male rats were divided into seven groups out of which groups 2-7 were made hyperlipidemic using poloxamer 407 (1.0 g/kg body weight) intraperitoneally. Groups 1, 2 and 3 were the normal, hyperlipidemic and standard drug control groups respectively, whereas groups 4-7 were the test groups. Results: C. sesamoides, M. flagellipes and P. mildbraedii inhibited alpha-amylase activity, while M. flagellipes and P. mildbraedii had activity against pancreatic lipase. The n-hexane fraction of P. mildbraedii and M. flagellipes inhibited both lipase and amylase enzyme activities among the four fractions of each plant tested. The GCMS analysis of n-hexane fractions revealed the presence of two major compounds in each plant which were 9-octadecenoic acid and hexadecanoic acid in P. mildbraedii, and hexadecanoic acid and 9,12-octadecadienoic acid in M. flagellipes. The in vivo studies revealed that the n-hexane fraction of P. mildbraedii and M. flagellipes significantly decreased (p < 0.05) total triglycerides, total cholesterol, and low density lipoprotein cholesterols when compared to the hyperlipidemic control rats. Conclusions: P. mildbraedii and M. flagellipes have the potency to act as antiobesity and anti-hyperlipidemic agents.